(untitled) (VETERINARIA, 2020)
The bovine herpesvirus-1 (BoHV-1) has a worldwide distribution. It is highly contagious and considered as the major pathogen in cattle herds. It is known to cause infectious bovine rhinotracheitis (IBR), abortion, infectious pustular vulvovaginitis (IPV), and infectious balanoposthitis (IBP) that result in great loss for the livestock sector. A cross-sectional study was carried out between the period of July 2016 to October 2016 to determine the seroprevalence and identify risk factors associated with bovine herpesvirus-1. Information regarding herd management was recorded through personal interviews with farmers. In total, 184 animals were sampled from 21 herds. Using the enzyme-linked immunosorbent assay (ELISA), the true prevalence was 31.17%. The multivariable random-effects logistic regression model revealed that animals aged between 2 and 5 years old were 12 times more likely to suffer IBR than younger animals (< 2 years) (OR=13.14; p=0.005). Thus, the older animals (> 5 years) were 11.8 times more likely to suffer IBR than the younger ones (OR=12.84; p=0.011). However, there was no significant effect of the herd size and origin of animals on odds of being IBR seropositive (p=0.078 and p=0.079 respectively). Based on these results, epidemiological control and prevention measures must be put in place to reduce the prevalence of this disease and ultimately eradicate it.